2018
DOI: 10.1159/000489210
|View full text |Cite
|
Sign up to set email alerts
|

Camel Milk Ameliorates 5-Fluorouracil-Induced Renal Injury in Rats: Targeting MAPKs, NF-κB and PI3K/Akt/eNOS Pathways

Abstract: Background/Aims: The clinical utility of 5-fluorouracil (5-FU) is limited by its nephrotoxicity. Camel milk (CM) has previously displayed beneficial effects in toxicant-induced nephropathies. The current study aimed to investigate the potential of CM to attenuate 5-FU-induced nephrotoxicity in rats. Methods: Renal tissues were studied in terms of oxidative stress, inflammation and apoptosis. The levels of renal injury markers, inflammatory cytokines along with NOX-1, Nrf-2 and HO-1 were assessed by ELISA. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 50 publications
13
46
0
Order By: Relevance
“…Numerous signaling pathways are involved in controlling apoptosis. Among them, NF‐κB p65 and p38‐MAPK are considered important intermediates for induction of apoptosis . NF‐κB represents a cornerstone of the inflammatory process during nephrotoxicity that is activated in response to ROS .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous signaling pathways are involved in controlling apoptosis. Among them, NF‐κB p65 and p38‐MAPK are considered important intermediates for induction of apoptosis . NF‐κB represents a cornerstone of the inflammatory process during nephrotoxicity that is activated in response to ROS .…”
Section: Discussionmentioning
confidence: 99%
“…Among them, NF-κB p65 and p38-MAPK are considered important intermediates for induction of apoptosis. [49,50] NF-κB represents a cornerstone of the inflammatory process during nephrotoxicity that is activated in response to ROS. [13,51,52] A recent study indicated that the expression of NF-κB was upregulated in the kidney of rats administered gentamicin.…”
Section: Discussionmentioning
confidence: 99%
“…Research teams continue to investigate the nephrotoxic mechanisms of different widely used chemotherapy drugs, with hopes that in the future a panel of specific renal biomarkers can be used as the gold standard for early renal injury detection. Previous studies investigated the effect of the most frequent chemotherapy agents used in clinical practice on tubular renal cells and the effect on renal biomarkers [139,140,141,142,143,144,145,146,147] (Table 1).…”
Section: Future Directions/perspective Regarding Kim-1 In Drug-indmentioning
confidence: 99%
“…The activation of AKT leads to serine 1177 phosphorylation of eNOS, which can upregulate the expression of eNOS. In addition, activation of the PI3K/AKT/eNOS pathway can inhibit apoptosis in vascular endothelial cells [15]. AKT plays an important role in reducing cardiomyocyte apoptosis and myocardial protection.…”
Section: Discussionmentioning
confidence: 99%